2013
DOI: 10.1021/cm400468u
|View full text |Cite
|
Sign up to set email alerts
|

Alkaline Stable C2-Substituted Imidazolium-Based Anion-Exchange Membranes

Abstract: The alkaline stability of imidazolium salts and imidazolium-based alkaline anion-exchange membranes (AEMs) was investigated in this work. C2-substituted (with methyl, isopropyl or phenyl groups) imidazolium salts, 3-ethyl-1,2-dimethyl imidazolium bromine ([EDMIm][Br]), 3-ethyl-2-isopropyl-1-methylimidazolium bromine ([EIMIm][Br]), and 3-ethyl-1-methyl-2-phenyl- imidazolium bromine ([EMPhIm][Br]), were synthesized and characterized. The effect of the C2-substitution on the alkaline stability of imidazolium salt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
212
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 284 publications
(229 citation statements)
references
References 68 publications
11
212
0
4
Order By: Relevance
“…They reported 48% degradation of C-2 unsubstituted 3-ethyl-1-methylimidazolium bromine exposed to 1 M KOH for 60 hours, while the C-2 substituted 3-ethyl-1,2-dimethylimidazolium bromine did not degrade even in 2 M KOH after exposure for 168 hours. 34 These experimental findings supported the modeling results of Wang and co-workers. 28 Marino and co-workers tested the half-life of imidazolium salts in 6 M sodium hydroxide, and they reported that the half-life of the C-2 unsubstituted 1-methyl-3-octyl-imidazolium was too short to measure at 60…”
supporting
confidence: 85%
See 2 more Smart Citations
“…They reported 48% degradation of C-2 unsubstituted 3-ethyl-1-methylimidazolium bromine exposed to 1 M KOH for 60 hours, while the C-2 substituted 3-ethyl-1,2-dimethylimidazolium bromine did not degrade even in 2 M KOH after exposure for 168 hours. 34 These experimental findings supported the modeling results of Wang and co-workers. 28 Marino and co-workers tested the half-life of imidazolium salts in 6 M sodium hydroxide, and they reported that the half-life of the C-2 unsubstituted 1-methyl-3-octyl-imidazolium was too short to measure at 60…”
supporting
confidence: 85%
“…Then, we compared the alkaline stability of these two AEMs. The second finding that we wanted to verify was that of Lin and coworkers, 34 who proposed that C-2 substituted (with a methyl group) imidazolium-based AEMs were much more stable in alkali when compared with C-2 unsubstituted imidazolium-based AEMs. To verify this finding, we compared the alkaline stability of AEMs made using C-2 substituted imidazole (1,2DMI) and C2 unsubstituted imidazole (1MI).…”
Section: Reduction Of the Ketone Group In Ppo-kc6br (Ppo-c6brmentioning
confidence: 93%
See 1 more Smart Citation
“…14, However, it has been shown that quaternary ammonium-based AEMs are sensitive toward Hofmann elimination 20,41 and direct nucleophilic elimination reactions 42,43 that result in loss of ion exchange capacity (IEC) and ionic conductivity. To resolve the stability problem inherent to quaternary-ammonium-group-containing AEMs, several alternative cations, including imidazolium, 41,44,45 benzimidazolium, 3,45,46 guanidinium, 15,47,48 phosphonium 8,9,49 and metal cations 50,51 have been proposed and investigated. Phosphonium-based AEMs were investigated by Gu et al 52 Gu et al attached benzyl-tris(2,4,6-trimethoxyphenyl) phosphonium (TTMPP + ) onto polysulfone backbone to make AEMs, and found them to be alkaline stable; There was no ionic conductivity fade after immersion in 1M KOH for 30 days at room temperature.…”
mentioning
confidence: 99%
“…C NaOH is the concentration of NaOH solution previously standardized by potassium hydrogen phthalate [64].…”
Section: Physicochemical Characterization Of Go Solution and Go/cs:pvmentioning
confidence: 99%